Evaluasi Kinerja Zona Selamat Sekolah (ZoSS) (Studi Kasus Yayasan Wakaf Al Kaffah Binjai) - Anwari Ginting, Jedi; Darlina Tanjung; Marwan Lubis (Universitas Nusa Putra, 2025)
The School Safety Zone (ZoSS) is designed to prevent accidents involving students when going to and from school. This research aims to determine the effect of inappropriate design and placement of markings and signs on ZoSS facilities based on visual observations of the speed of passing vehicles, crossing safety, and the level of conformity of ZoSS at the Alkaffah Binjai Waqf Foundation with established standards. The method used is to compare the results of field studies with the Directorate General of Land Transportation Standards, as well as using normal distribution statistical analysis (Z test). This research found that the DS value of the road is 0.45, which indicates that the road has a type C road service level. Speed the average number of vehicles passing on Jalan LetJend Jamin Ginting at the Alkaffah Binjai Wakaf Foundation ZoSS is: In the morning 35.44 km/hour (direction Binjai-Tanah Seribu) and 34.53 km/hour (direction Tanah Seribu-Binjai); In the afternoon 36.44 km/hour (direction Binjai-Tanah Seribu) and 38.91 km/hour (direction Tanah Seribu-Binjai). This speed still exceeds the permitted speed limit, namely 30 km/hour. The Z Test analysis of the characteristics of the waders in ZoSS shows that the calculated Z value (2.170) is greater than the Z table, which concludes that the waders in ZoSS are quite safe. However, the results of field observations showed that the signs were incomplete, their position was incorrect, and the road markings were damaged. These findings indicate that the ZoSS design in the field is not fully in accordance with the Directorate of Land Transportation Standards so it needs to be redesigned. The output of this research is a proposal to redesign ZoSS at the Alkaffah Binjai Waqf Foundation to be more in line with standards and improve safety for pedestrians, especially school students.